Investigating the Impact of a Treadmill Transfer Bed (TTB) on Enhancing the Safety of Patient Transfers (Development Engineering Conferences Center Articles Database, 2025)
Manual patient transfer is one of the most frequent activities in healthcare, yet it poses significant risks of musculoskeletal disorders for medical staff and potential injuries, such as falls, for patients. Current transfer aids often fail to adequately address these issues, necessitating a technological solution. This project introduces the design and evaluation of an innovative Treadmill Transfer Bed (TTB), a semi-automated device engineered to improve the safety and efficiency of transferring patients from one surface to another. The TTB utilizes a unique mechanism combining a motorized, low-speed, high-torque conveyor belt with a linear sliding system. This design allows a single operator to slide the conveyor surface under the patient and transfer them smoothly without any lifting or manual repositioning, thereby minimizing physical strain on caregivers and eliminating dangerous patient movements. This paper outlines the design of a prototype and proposes a methodology for its evaluation in a clinical simulation environment using standardized mannequins to assess key performance indicators such as transfer time, safety, and operator workload. The development of the TTB aims to reduce patient fall risks, decrease the need for extra personnel, and enhance the overall safety and modernization of patient care protocols.